2020
DOI: 10.1002/jcla.23172
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAE330013P06 promotes progression of breast cancer with type 2 diabetes

Abstract: Background In previous research, we found diabetes rather than obesity was an independent risk factor of breast cancer. However, why diabetes could lead to increased risk of breast cancer patients remains elusive. Long non‐coding RNAE330013P06 has been shown to be upregulated in diabetes, and long non‐coding RNAs generally promote progression of cancer. Methods About 200 specimens of breast patients were obtained in previous clinical trial; 34 samples diagnosed as type 2 diabetes in breast cancer patient were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Another study showed that expression levels of miR-124a and miR-30d were the highest in the blood of breast cancer patients with T2DM compared to the T2DM patients and breast cancer patients and the lowest in the healthy group, indicating that miR-124a and miR-30d could contribute to the development of breast cancer in patients with T2DM [144]. In addition, found to be upregulated in the plasma of T2DM patients, high serum LncRNAE330013P06 expression levels were also associated with breast cancer progression, family history, and lymph node metastasis compared with non-T2DM patients, T2DM patients without breast cancer, and healthy donors [145]. However, so far, no circulating miRNA and LncRNA expression profiling has been correlated to TNBC in T2DM patients, in comparison to TNBC patients and T2DM patients.…”
Section: Cell-free Mirnas and Lncrnasmentioning
confidence: 91%
“…Another study showed that expression levels of miR-124a and miR-30d were the highest in the blood of breast cancer patients with T2DM compared to the T2DM patients and breast cancer patients and the lowest in the healthy group, indicating that miR-124a and miR-30d could contribute to the development of breast cancer in patients with T2DM [144]. In addition, found to be upregulated in the plasma of T2DM patients, high serum LncRNAE330013P06 expression levels were also associated with breast cancer progression, family history, and lymph node metastasis compared with non-T2DM patients, T2DM patients without breast cancer, and healthy donors [145]. However, so far, no circulating miRNA and LncRNA expression profiling has been correlated to TNBC in T2DM patients, in comparison to TNBC patients and T2DM patients.…”
Section: Cell-free Mirnas and Lncrnasmentioning
confidence: 91%